2021
DOI: 10.26553/jikm.2021.12.1.21-37
|View full text |Cite
|
Sign up to set email alerts
|

Primary Dysmenorrhea Risk based on Characteristics, Dietary Habits, and Types of Exercise

Abstract: The young woman’s frequent complaint related to reproduction health is dysmenorrhea. The incidence of primary dysmenorrhea is affected by various factors. The purpose of the study was to examine the factors affecting primary dysmenorrhea, including characteristics, dietary habits, and types of exercise. The research was quantitative research employing correlational analytic method with a cross-sectional approach. The samples of the study were 97 female college students of The Faculty of Sports and Health Educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A highly significant association was found between the consumption of refined grains, sweet snacks, bakery items, street food, carbonated beverages, frozen meat items and fast food consumption with menstrual abnormalities which is consistent with findings of other studies. 22 , 23 However, Rupa and coworkers did not find significant association between junk consumption with menstrual abnormalities. 24 An interesting finding of present study is that among all categories of junk food items no significant association was found between the consumption of salty snacks and frozen meat items with menstrual disorders.…”
Section: Discussionmentioning
confidence: 98%
“…A highly significant association was found between the consumption of refined grains, sweet snacks, bakery items, street food, carbonated beverages, frozen meat items and fast food consumption with menstrual abnormalities which is consistent with findings of other studies. 22 , 23 However, Rupa and coworkers did not find significant association between junk consumption with menstrual abnormalities. 24 An interesting finding of present study is that among all categories of junk food items no significant association was found between the consumption of salty snacks and frozen meat items with menstrual disorders.…”
Section: Discussionmentioning
confidence: 98%
“…There is a lack of physical activity, but enacting regulations to keep people active at home has also led to eating mistakes among young women, such as snacking heavily, trying new dishes, and ordering food through apps. This eventuality has led to an increase in young women who are obese, especially in central obesity (6). Central obesity, in particular, is characterized by bloating caused by the accumulation of abdominal fat.…”
Section: Discussionmentioning
confidence: 99%
“…As new habits and characteristics change with the increase of time at home, during the COVID-19 epidemic, young women, especially female college students, have an increased incidence of overweight and obesity. They are not only conducting online learning activities at home, but they are also munching more, trying new recipes, ordering meals through apps, and doing less exercise (6,7). Robinson, Boyland, and Chisholm et al (2021) stated that the reduction in physical activity has led to young people in the United States and the world engaging in physical activity, and overweight female cases have increased, especially in developing countries such as Indonesia (8).…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, 54.89% of women suffer from primary dysmenorrhea, while the remaining population experiences secondary dysmenorrhea (Joshi et al, 2015). Dysmenorrhea is accompanied by common symptoms such as back pain, fatigue, irritability, and anxiety, which undoubtedly hinder the training process and impede performance during competitions (Fitrianingsih & Santanu, 2021). In fact, a study by Reiko et al (2021) revealed that 85.6% of female athletes from various sports experienced dysmenorrhea, with 27.8% reporting mild pain, 19.3% experiencing moderate pain, and a significant 52.9% enduring severe pain.…”
Section: Introductionmentioning
confidence: 99%